Clinical information seeking in traumatic brain injury: a survey of Veterans Health Administration polytrauma care team members. (12th December 2017) - Hogan, Timothy; Martinez, Rachael; Evans, Charlesnika; Saban, Karen; Proescher, Eric; Steiner, Monica; Smith, Bridget
Abstract: Background: The polytraumatic nature of traumatic brain injury (TBI) makes diagnosis and treatment difficult. Objectives: To (1) characterise information needs among Veterans Health Administration (VHA) polytrauma care team members engaged in the diagnosis and treatment of TBI; (2) identify sources used for TBI related information; and (3) identify barriers to accessing TBI related information. Methods: Cross‐sectional online survey of 236 VHA polytrauma care team members. Results: Most respondents (95.8%) keep at least somewhat current regarding TBI, but 31.5% need more knowledge on diagnosing TBI and 51.3% need more knowledge on treating TBI. Respondents use VHA affiliated sources for information, including local colleagues (81.7%), VHA offsite conferences/meetings (78.3%) and onsite VHA educational offerings (73.6%); however, limited time due to administrative responsibilities (50.9%), limited financial resources (50.4%) and patient care (50.4%) were prominent barriers. Discussion: Medical librarians are in a unique position to develop information services, resources and other electronic tools that reflect the clinical context in which polytrauma care team members practice, and the different tasks they perform. Conclusion: Polytrauma care team members could benefit from additional information regarding the diagnosis and treatment of TBI. Addressing their information needs and supporting their information seeking requires a mulit‐pronged approach to time and financial constraints.